Approaches to promoting the appropriate use of antibiotics through hospital electronic prescribing systems: a scoping review. (20th May 2016) - Cresswell, Kathrin; Mozaffar, Hajar; Shah, Sonal; Sheikh, Aziz
Abstract: Objective: To identify approaches of using stand-alone and more integrated hospital ePrescribing systems to promote and support the appropriate use of antibiotics, and identify gaps in order to inform future efforts in this area. Methods: A systematic scoping review of the empirical literature from 1997 until 2015, searching the following databases: MEDLINE, EMBASE, Cochrane Database of Systematic Reviews, Google Scholar, Clinical Trials, International Standard Randomised Controlled Trial Number Registry, Economic Evaluation database and International Prospective Register of Systematic Reviews. Search terms related to different components of systems, hospital settings and antimicrobial stewardship. Two reviewers independently screened papers and mutually agreed papers for inclusion. We undertook an interpretive synthesis. Key findings: We identified 143 papers. The majority of these were single-centre observational studies from North American settings with a wide range of system functionalities. Most evidence related to computerised decision support (CDS) and computerised physician order entry (CPOE) functionalities, of which many were extensively customised. We also found some limited work surrounding integration with laboratory results, pharmacy systems and organisational surveillance. Outcomes examined included healthcare professional performance, patient outcomes and health economic evaluations. We found at times conflicting conclusions surrounding effectiveness, which may be due to heterogeneity of populations, technologies and outcomes studied. Reports of unintended consequences were limited. Conclusions: Interventions are centred on CPOE and CDS, but also include additional functionality aiming to support various facets of the medicines management process. Wider organisational dimensions appear important to supporting adoption. Evaluations should consider processes, clinical, economic and safety outcomes in order to generate generalisable insights into safety, effectiveness and cost-effectiveness.